Penerapan Aplikasi Mobile Berbasis Edukasi dan Self-Care dalam Meningkatkan Kualitas Hidup Pasien CKD Stage V di RS Tk.II dr. Soedjono - Endro Haksara; Ainurr Rahmanti; Margiyati Margiyati; Sheikha Raissa; Mareta Sukma (The Journal General Health and Pharmaceutical Sciences Research, 2025)
Stage V chronic kidney disease (CKD) is a serious health challenge in Indonesia due to its increasing prevalence and high cost of treatment. Educational efforts and the implementation of digital technology-based self-care, particularly through mobile applications, are considered to have the potential to improve patients' quality of life. This study aims to evaluate the effectiveness of educational and self-care-based mobile applications on the quality of life, knowledge, self-efficacy, and medication adherence of stage V CKD patients undergoing treatment at Dr. Soedjono Class II Hospital. The study used a quasi-experimental design with a pretest–posttest control group approach. From a population of 185 patients, 140 respondents were divided into intervention (n=70) and control (n=70) groups. The intervention included the use of a mobile application equipped with health education features, medication reminders, symptom monitoring, and communication with medical personnel. The results showed that the intervention group experienced significant improvements compared to the control group, including quality of life (+12.6 vs +4.2; p<0.01), knowledge (+16.5 vs +5.7; p<0.001), self-efficacy (+9.3 vs +3.1; p<0.01), and medication adherence (+1.2 vs +0.4; p<0.01). Furthermore, the frequency of application use at least four times per week was positively associated with improved quality of life (r=0.41; p<0.01). These findings demonstrate that mobile applications can be an effective and cost-effective strategy to support the management of stage V CKD patients in Indonesia.